Penggunaan Media Instagram sebagai Media Dakwah dan Wirausaha Mahasiswi Prodi KPI STIBA Ar Raayah - Khatimah, Husnul; Tiani, Windy; Sari, Tika Gusnita; Ulhana, Syifa (Jurnal Keislaman, 2024)
Instagram with its variety of interesting features is currently a forum for the spread of da'wah and entrepreneurship, especially among students. The purpose of this research is to see how the use of Instagram as a media for da'wah and entrepreneurship among female students of KPI STIBA Ar Raayah Sukabumi. This research uses a field research method with a qualitative approach, with a sample of 5 female students of KPI STIBA Ar Raayah Sukabumi Batch 3. The results showed that the use of Instagram played a significant role in the spread of da'wah and entrepreneurship during the even semester holidays and did not play a role in the campus environment, given the campus rules that limit the use of electronic devices in the context of boarding life.